REACTION OF Cr, Cr2, Mn, Mn2, Fe, AND Fe2 WITH F2, H2, N2, AND O2: A DENSITY FUNCTIONAL THEORY STUDY - Wijaya (NIM 10500017), Berlin
ABSTRACT: Information about transition metal reaction is important to understand the catalytic processes. From this study, it can be concluded that chromium atom and dimer could react with F2, H2, dan O2. CrH2 and Cr2H2 have lower reaction energy than CrF2, Cr2F2, CrO2 and Cr2O2. Manganese atom react only with F2 and H2 however its dimer react with F2, H2, and O2. Both iron atom and dimer could react with F2, N2 and O2. Iron atom or dimer compounds with oxygen gas have lower stabilization energy (0.55 and 2.69 eV) than chromium-O2 or manganese-O2 compounds and the stability increase from iron atom to dimer. All calculations were carried out using computational method with Density Functional Theory using 6-311 plus G(d,p) basis set and B3LYP level of theory.